Transumanismo e melhoramento genético: fundamentos, aplicações e críticas - Morais, Cassiano de Souza (2025)
This dissertation aims to investigate and clarify the scope and significance of the transhumanist movement in contemporary society. This movement advocates for the ethical and responsible development and use of emerging technologies to enhance the human condition through genetic engineering. However, it has sparked significant bioethical debates and controversies regarding concepts such as eugenics, genetic manipulation, and its implications for human nature. To address these issues, we examine humanity's quest for immortality throughout various historical periods and explore the foundations of the transhumanist movement, along with the trajectory of technological development – from the most rudimentary techniques to the advent of Genetically Modified Organisms (GMOs), which have been applied over time to plants, animals, and now humans. Finally, we analyze the criticisms directed at the movement over time, focusing primarily on the perspectives of Hans Jonas, Jürgen Habermas, and Michael Sandel. Their arguments and starting points are highlighted, culminating in a discussion of how transhumanists respond to these critiques and the foundational arguments that support their perspectives.